2021
DOI: 10.3390/microorganisms9040773
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Lactic Acid Bacteria for the Bio-Control of Botrytis cinerea and the Potential of Lactiplantibacillus plantarum for Eco-Friendly Preservation of Fresh-Cut Kiwifruit

Abstract: Botrytis cinerea, responsible for grey mold, represents the first biological cause of fruit and vegetable spoilage phenomena in post-harvest. Kiwifruit is a climacteric fruit particularly prone to this mold infestation during storage. Lactic acid bacteria (LAB) are food-grade bacteria that can synthesize several metabolites with antimicrobial activity and are, therefore, suggested as promising and eco-friendly resources for the bio-control of molds on fruits and vegetables. In this work, we propose the screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 65 publications
(55 reference statements)
2
21
0
1
Order By: Relevance
“…The sensory attributes of the ground beef were evaluated. The color and overall acceptability were scored at 8, corresponding to “ like very much ,” whereas odor scored 7 “ liked moderately .” Sensory evaluation (by trained panelists) of kiwifruit chunks dip in CFS Lactiplantibacillus plantarum UFG 121 and stored at 4°C concluded that kiwifruit quality was remained for marketing after 10 days and was similar to control fruits (without CFSl; De Simone et al., 2021). These results indicate that the use of CFS as an antimicrobial has low effects on sensory acceptability.…”
Section: Antimicrobial Activity Of Cfss On Foodsmentioning
confidence: 99%
“…The sensory attributes of the ground beef were evaluated. The color and overall acceptability were scored at 8, corresponding to “ like very much ,” whereas odor scored 7 “ liked moderately .” Sensory evaluation (by trained panelists) of kiwifruit chunks dip in CFS Lactiplantibacillus plantarum UFG 121 and stored at 4°C concluded that kiwifruit quality was remained for marketing after 10 days and was similar to control fruits (without CFSl; De Simone et al., 2021). These results indicate that the use of CFS as an antimicrobial has low effects on sensory acceptability.…”
Section: Antimicrobial Activity Of Cfss On Foodsmentioning
confidence: 99%
“…MQT16M1 was also studied for its antifungal activity against Botrytis and was shown to reduce mycelial growth reduction by 90%, owing to the production of VOCs, such as phenylethyl alcohol [145,146]. Finally, lactic acid bacteria like Lactiplantibacillus plantarum UFG 121 have also been shown to have antifungal activity against B. cinerea, reducing its concentration by 40-80%, and this has been associated with a pH reduction, probably due to the production of phenyllactic acid and 4-hydroxyphenyllactic acid [147,148].…”
Section: Synthesis Of Volatile Organic Compoundsmentioning
confidence: 99%
“…In addition, LAB reduce the toxic agents in wheat and maize grains produced by the filamentous fungi [ 46 , 47 , 53 ]. De Simone and co-workers demonstrated that the Lactiplantibacillus plantarum species exerted strong antagonism against the necrotrophic fungus Botrytis cinerea [ 54 ]. Grey mold B. cinerea , an etiological agent, is a typical contaminant of many horticultural crops.…”
Section: Antifungal Activity Of Labmentioning
confidence: 99%
“…Lactobacillus sucicola and Pediococcus acidilactici showed antifungal activity against P. digitatum and other pathogenic species [ 48 ]. Several authors reported that LAB exhibits antifungal activity against horticultural and fruit crops [ 38 , 49 , 50 , 51 , 54 ]. On the other hand, Li et al, demonstrated that edible films embedded with 2% LAB prolong shelf life and prevent banana blackening [ 52 ].…”
Section: Antifungal Activity Of Labmentioning
confidence: 99%